Enterohaemorrhagic Escherichia coliO157:H7 target Peyer's patches in humans and cause attaching/effacing lesions in both human and bovine intestine. Issue 3 (1st September 2000) - Phillips, A D; Navabpour, S; Hicks, S; Dougan, G; Wallis, T; Frankel, G
Abstract : BACKGROUND: Enterohaemorrhagic Escherichia coli (EHEC) constitute a significant risk to human health worldwide, and infections, particularly with serogroup O157:H7, are associated with consumption of a variety of food and water vehicles, particularly food of bovine origin. EHEC cause acute gastroenteritis, bloody diarrhoea, and haemorrhagic colitis; up to 10% of cases develop severe complications, including the haemolytic uraemic syndrome, with a 5% case fatality. A virulence characteristic of enteropathogenic E coli, the attaching/effacing lesion, is considered to be important in EHEC. However, although EHEC produce this lesion on cultured human cells, this has not been demonstrated on human intestinal mucosal surfaces. In addition, the initial site(s) of colonisation of EHEC in humans is not known. AIMS: To assess the association of EHEC O157:H7 with paediatric and bovine intestine using in vitro organ culture and determine if attaching/effacing lesions occur. METHODS: Ultrastructural analysis of in vitro intestinal organ cultures of human small and large intestine was used to investigate adhesion of O157:H7 EHEC to intestinal surfaces. Bovine intestinal organ culture was used to examine the pathology produced by the same EHEC strain in cattle. RESULTS: The study showed that EHEC O157:H7 adhered to human intestinal mucosa. Binding and attaching/effacing lesion formation of O157:H7 in humans was restricted to follicle associated epithelium of Peyer's patches. The same strain caused attaching/effacing lesions on bovine mucosa. CONCLUSIONS: O157:H7 targets follicle associated epithelium in humans where it causes attaching/effacing lesions. The same human isolate can cause attaching/effacing lesions in cattle, indicating that similar pathogenic mechanisms operate across human and bovine species